KORELASI TINGKAT PENDIDIKAN DENGAN PARTISIPASI PEMILIH PEMULA DALAM PEMILU NASIONAL SERENTAK 2019 DI KABUPATEN INDRAGIRI HULU - Yusnedi, Yusnedi; Utami, Sabrina (LPPM Press STIE Indragiri Rengat, 2019)
Abstract     This research is in Indragiri Hulu Regency, which is specialized in Rengat District. The purpose of this study is to determine how the correlation between the level of education with the participation of novice voters in the 2019 Election in Indragiri Hulu Regency. This research used quantitative methods, with descriptive analysis. The sample in this study were novice voters in Rengat District, Indragiri Hulu Regency, with total 1072 people. By using the Slovin formula, 91 samples were obtained. This research used primary data types. The analytical tool used in this study is by using Simple Linear Regression Analysis with the help of SPSS version 20. The results of this study indicate that the level of education has a correlation with the participation of novice voters in Rengat District, Indragiri Hulu Regency.   Keywords: Level Education, Novice Voter Participation, Election